Reflection as a Way to Grapple TPACK Complexity for EFL Teachers - Yunica Rhosiana Sari; Sumardi Sumardi (BIRCU, 2020)
Technological Pedagogical Content Knowledge (TPACK) is a framework to develop the theory to practice in teaching with technology. Therefore, the teacher, as a practitioner of TPACK implementation, has a responsibility to implement the knowledge effectively. This study investigates the meta-cognitive awareness produced by teachers who participate in TPACK lesson design workshops. This process involves some reflection tools, focus group discussion, and reflective journal as a platform for doing the reflection. This study documented teachers’ stories during three interviews as they created their TPACK lesson design. The detailed data was from three Indonesian teachers. Those teachers participated in the process of research from the professional development workshop to the focus group interview. The data indicated the details of their experience in reflecting and determining on their professional knowledge. These findings show that during the reflection, the teachers start to realize each aspect of TPACK in three stages. These findings are useful for the government to establish professional development workshops in the technology education field. The researcher explored the implications of this analysis for teachers to effectively design the lesson and future researchers.